The Correlation Factors of Washing Technique Equipment With Health Cutlery in Delicatessens In The Work Area Port Health Office Samarinda - Ningsih, Riyan; Widyasari, Octy; K, Iriyani (Universitas Ahmad Dahlan, 2015)
Hygiene of food and beverages is influenced by cutlery. Behavioral factor related to the food management is an important factor in food hygiene. The purpose of this study is to determine the relationship of knowledge and washing techniques practice with the hygiene tableware at food stalls.The design of this study was Cross-sectional. The study was conducted in food stall at the Port Health Office Samarinda using observation method completed by cutlery hygiene inspection. The research samples were 4 to 5 tableware and 30 samples of food handlers. Mann Whitney test was used as the data analysis.The findings showed that there was no relationship between knowledge and hygiene of utensils (Ï value = 0370), while there was a relationship between the practice of cleanliness of cutlery (Ï value = 0.002) in food stall at The Port health Office area in Samarinda.Suggestions for food handlers are to soak the cutlery in advance so that the rest of the food stuck or the hardened part can be easily off and cleaned. Do the rinsing with the running water or frequently replace the rinse water. Re-clean the cutlery using a clean cloth or frequently replaced and keep cutlery in proper place, avoid the dust and dirt. To the related institutions are expected to do the regular inspection of the cutlery, do the monitoring and evaluation to coaching and training and the need of local regulations governing cleanliness of food stalls in the port authority.Â Keywords: the Health of Cutlery, Knowledge, Behavior, Practice